Análise investigativa de polimorfismos genéticos associados à suscetibilidade da infecção da dengue em pacientes do Brasil - Cansanção, Isaac Farias (2015)
Dengue is an infectious disease that is associated with high morbidity and mortality rates in tropical and subtropical countries. Infection can be asymptomatic or have warning signs leading to severity. The diversity of these episodes can be affected mainly by the ratio of serotypes/genotypes of the virus. Different interleukins are directly associated with dengue infection, and they are closely related to the immunopathogenesis of the disease. Genetic polymorphisms of these cytokines may be responsible for the imbalance of the inflammatory process and markers for dengue susceptibility and may be related to dengue symptoms. In this study, single nucleotide polymorphisms (SNPs) of the interleukins (IL) IL1β -511C>T, IL1RN bp VNTR 86, IL6 -174G>C and IL10 -819C>T and TNFα -308G>A were analyzed in a group of 198 individuals with suspected dengue infection, during August 2011 to August 2013. Dengue was confirmed in 118 patients, and the control group consisted of another 80 individuals without dengue. Clinical and epidemiological data were collected from medical records or personal interviews. The genotype frequencies of all SNPs analyzed were found to be in Hardy-Weinberg equilibrium (HWE), except for the TNFα gene. The major finding was the association of the IL1β (-511C>T) T allele with dengue susceptibility (p <0.05). Analysis of association showed that the presence of the IL6 (-174G>C) polymorphic allele showed an increase in dengue susceptibility combined with at least a polymorphic allele of TNFα and with IL1β (-511C>T) polymorphic allele. Also, the heterozygous genotype of IL10 (-819 C>T) was significantly associated with TNFα (-308G>A) and IL1β (-511C>T) with IL1RN homozygous polymorphic genotypes for both, respectively. Considering the clinical symptoms, only dizziness was found to be associated with the T allele IL1β (-511C>T) (P = 0.01). Our data showed the importance of IL1β (-511C>T) polymorphism for dengue susceptibility and highlighted the additive effect of some interleukins. Also shown was that this polymorphism can be a marker for dengue symptoms, which may be relevant for therapeutic approaches.